Assessment of quality assurance of existing practices on APEL for TVET teacher training (TVET-TT) among the participating RCB member countries - Md Yunos, Jailani (2013)
Accreditation of Prior Experimental Learning (APEL) is relatively a new concept in Malaysia higher education institutions although it has been broadly practiced and well recognized in several countries across the globe such as South Africa, Australia and America. Due to its under exposure in Malaysia, a research has been done in order to get a better understanding of how APEL should be implemented in Malaysia specifically on teacher training. The aim of this research is to assess the quality assurance of existing practices on APEL for TVET teacher training (TVET-TT) among the participating RCP partner countries including Malaysia. This research is mainly a qualitative study involving several methods which are document analysis, thematic analysis and focus group discussion. The document analysis was conducted to identify the gap practices based on the similarities and differences in the APEL practices anlong the participating countries. For the thematic analysis, interviews with officers from the Open University Malaysia and the Malaysia Qualification Agency had been carried out to identify the APEL practice within the context of Malaysia. Apart from that, several focus group discussions were conducted to validate the APEL framework involving Wawasan Open University representing Malaysia as well as from research counterparts and several ASEAN co~mtriesn amely Indonesia, Laos and Cambodia. Based on the findings from the above-mentioned analyses, a general framework on APEL process was created. The APEL framework developed was a generic and therefore, the participating countries will modify according to their needs and policy. This newly developed APEL framework has significant implications on the TVET teaching training programs from the aspect of acquisitions teacl~ersw ith industrial ready skills and shortens of the training durations. In the nutshell, this APEL framework can be used as a guideline or reference for the iinplenlentation of APEL, however, some modifications are still required to fine-tune this general fraillework for better implementation in the future. Where there has been research, the findings suggest that there is still a lack of awareness, clarity about the nature, value and purpose of RPL and institutional bureaucracy and inexperience, and the absence of expertise in assessment of experiential learning remain constraining factors for widespread implementation of APEL-RPL in Malaysia (Kaprawi, Razzaly, Raja (2010). While APEL-RPL implementation is in the process of maturing in Malaysia, an important question that needs to be dealt with urgently, is 'what guarantees are there that institutions are offering a quality assured programme of APEL. With its implementation of APEL-RPL, be it limited; thus quality assurance remaitls an issue to be dealt with. Of particular importance, there is an urgency to assess the quality assurance of existing practices on APEL for TVET teacher training (TVET-TT) in participating countries. It is believed that while some participating RCP member countries may be in similar developn~ental stage as Malaysia, some may have advanced further in implementing RPL and its quality assurance. Thus, experience and expert sharing with participating RCP member countries is crucial in setting up a benchmark APEL of TVET-TT for Malaysia and similar participating members.